Legal Pluralism and Indigenous Land Rights Conflicts in Eastern Indonesia - Zulfikar Ahmad Fikri; Prisca Agustinus Putri (JUSTISIA GLOBAL EDUKASI, 2026)
The recognition of indigenous peoples’ land rights remains one of the most significant sociolegal challenges in Indonesia, particularly in the eastern regions where customary land tenure systems continue to play a central role in community life. This study examines the relationship between legal pluralism and indigenous land rights conflicts in Eastern Indonesia by analyzing the interaction between state law, customary law, and local governance practices. Using a sociolegal research approach, the study explores how overlapping legal systems influence the emergence, escalation, and resolution of land disputes involving indigenous communities, government institutions, and private investors. The findings indicate that legal pluralism provides opportunities for recognizing local norms and cultural identities but simultaneously creates legal uncertainty when formal regulations fail to accommodate customary claims adequately. Conflicts frequently arise due to inconsistencies in land registration systems, competing interpretations of ownership rights, and unequal power relations between stakeholders. The study further reveals that indigenous communities often face barriers in asserting their land rights within formal legal institutions despite constitutional recognition of customary communities. Effective conflict resolution requires greater harmonization between state legal frameworks and customary governance mechanisms. The research argues that strengthening participatory decision-making processes, improving legal recognition of customary territories, and enhancing institutional coordination can reduce land-related conflicts and promote social justice. The study concludes that a balanced approach to legal pluralism is essential for ensuring legal certainty, protecting indigenous rights, and fostering sustainable development in Eastern Indonesia. These findings contribute to sociolegal scholarship by highlighting the importance of integrating cultural diversity into legal governance and land administration policies.